Decentralized Resilient Finite-Time-Control for Large-Scale Power Systems via Dynamic Triggering Against Deception Attacks - Liu, Yuezhi; Chen, Yong (IEEE transactions on smart grid, 2023)
This paper investigates the decentralized resilient finite-time control with the dynamic event-triggered mechanism for the large-scale power systems subject to deception attacks. Firstly, to save the network resource of the interconnected synchronous generators, the decentralized dynamic event-triggered mechanism (DDETM) is formulated, with the aid of the internal variable, the conservatism of the triggering condition is reduced. Secondly, to improve the resilience of the large-scale power system with respect to the deception attacks, the decentralized resilient finite-time controller (DRFTC) is constructed, in which, the sign function is applied in the controller design and the neural-network adaptive law formulation, obtaining faster convergence rate and precision. It is shown moreover that fast finite-time stability of the closed-loop power system can be obtained. Finally, simulation results manifest the validity of the proposed decentralized resilient finite-time controller.